Florina Ilis - Cristina Balinte (Revista de Istorie și Teorie Literară)
The Romanian Literature published after the year 2000 is especially characterized by the emergence of a new generation of writers, most of them born and educated during the last decades of communism. As a consequence of cultural openness manifested in the 90’s, a fruitful period of takeovers of world literature thought a large amount of translations, they managed to win the international literary market by adopting the writing style of influence and success in the West, and – a very important detail – by adapting the content of their daily literary readings at the local realities. Coming from the Transylvanian region, Florina Ilis is considered one of the most talented and the best rated Romanian (still) young novelists. Her books have been appreciated by critical reviewers, awarded and proposed to be translated into foreign languages. The herein contribution describes and examines in the form of a dictionary item, this prodigious literary activity, performed in the era of globalization.